Optimization of longitudinal electron beam properties for linac-based infrared free-electron laser at Chiang Mai University - Suphakul,S. (Elsevier BV, 2015)
A study to upgrade the linear accelerator system at the Plasma and Beam Physics (PBP) Research Facility at Chiang Mai University (CMU) to be an injector system for an infrared free-electron laser (IR FEL) is underway. The current PBP linac system consists of an S-band thermionic cathode RF-gun, a bunch compressor in a form of alpha-magnet and a SLAC-type linear accelerating structure. Since characteristics of the emitted FEL light strongly depend on electron beam properties, a dedicated work to develop and optimize the injector system to drive the FEL is particularly important. In this paper, the results of numerical study to optimize the longitudinal electron beam properties as well as some preliminary results of FEL simulations are presented and discussed. © 2013 The Authors.